Implementation of the New MABIMS Crescent Visibility Criteria: Efforts to Unite the Hijriyah Calendar in the Southeast Asian Region - maskufa maskufa; Sopa Sopa; Sri Hidayati; Adi Damanhuri (Universitas Islam Negeri Jakarta, 2022)
This paper discussed the implementation of the new MABIMS hilāl visibility criteria in the unification of the Hijriyah calendar in member countries (Malaysia, Brunei, Indonesia and Singapore). This research uses the approach of Astronomy and Grindle's theory of policy implementation. The data source comes from the MABIMS Muzakarah results document and related articles. The research results indicate that the new MABIMS moon crescent visibility criteria are part of a public policy that, in its implementation, requires two mutually supportive variables. First, the content of the policy in the form of the moon crescent visibility criteria (3⁰; 6.4⁰) was accepted by all member countries through the signing of an ad referendum on 8 December 2021. This acceptance will receive public support if it is beneficial to time management. Second, the context of implementation is carried out in stages by taking into the characteristics of the institutions involved in preparing the Hijriyah calendar. At the practical level, the policy can be well received by the public, except in Indonesia, which still faces obstacles. This is due to the policy in the three countries being carried out on a top-down basis, while in Indonesia, it is carried out on a bottom-up basis. Furthermore, determining of Ramadan, Shawwal, and Zulhijjah are still waiting for confirmation of the sighting of the moon (ru’yah). It related to the domination of ru’yah, and a strong distinction between the function of the calendar in civil administration and worship practice. Abstrak Makalah ini membahas penerapan kriteria baru visibilitas hilalMABIMS dalam penyatuan penanggalan Hijriyah di negara-negara anggota(Malaysia, Brunei, Indonesia dan Singapura). Penelitian ini menggunakanpendekatan penerapan kebijakan Astronomi dan teori Grindle. Sumber databerasal dari dokumen hasil Muzakarah MABIMS dan artikel terkait. Hasilpenelitian menunjukkan bahwa kriteria baru visibilitas hilal MABIMS merupakanbagian dari kebijakan publik yang dalam pelaksanaannya membutuhkandua variabel yang saling mendukung. Pertama, isi kebijakan berupa kriteriavisibilitas bulan sabit (3⁰; 6.4⁰) diterima oleh seluruh negara anggota melaluipenandatanganan referendum pada 8 Desember 2021. Penerimaan ini akanmendapat dukungan publik jika bermanfaat hingga manajemen waktu. Kedua,konteks pelaksanaannya dilakukan secara bertahap dengan memperhatikankarakteristik lembaga yang terlibat dalam penyusunan penanggalan Hijriyah.Pada tataran praktis, kebijakan tersebut dapat diterima dengan baik olehmasyarakat, kecuali di Indonesia yang masih menghadapi kendala. Hal inidisebabkan kebijakan di ketiga negara dilakukan secara top-down, sedangkan diIndonesia dilakukan secara bottom-up. Selanjutnya, penentuan awal Ramadan,Syawal dan Zulhijah masih menunggu konfirmasi penampakan hilal (rukyah).Ini terkait dengan dominasi ru’yah, dan perbedaan yang kuat antara fungsipenanggalan dalam administrasi sipil dan praktik ibadah.